(untitled) (Texas Journal of Agriculture and Biological Sciences, 2025)
This study investigated the relationship between hematological and biochemical blood parameters and aerobic capacity in young male and female athletes. The findings revealed a significant correlation between red blood cell parameters (RBC, hemoglobin [HGB], and hematocrit [HCT]) and key indicators of aerobic capacity, including VO2max, anaerobic threshold (AP), and oxygen utilization efficiency (VO2/YYQ). Additionally, it was observed that lower levels of urea, total bilirubin, and iron in the blood were associated with a higher heart rate at the anaerobic metabolism threshold. The study underscores the importance of monitoring hematological and biochemical parameters to better understand and enhance athletic performance in young athletes, while also highlighting the need for genderspecific approaches in training and physiological assessment